Dispositional Awe and Online Altruism: Testing a Moderated Mediating Model - Lin, RongMao; Chen, YanPing; Shen, YiLin; Xiong, XiaXin; Lin, Nan; Lian, Rong (Frontiers in Psychology, 2021)
Dispositional awe has a positive effect on pro-sociality. However, it has not been tested whether this trait appears in online altruism. Using a large sample of 3,080 Chinese undergraduates, this study tested a moderated mediating model that takes self-transcendent meaning in life (STML) as a mediator and subjective socioeconomic status (SSES) as a moderator. As predicted, dispositional awe was positively correlated with online altruism, partly via the indirect effect of STML. SSES moderated both the direct and indirect effects. Specifically, the predictive effects of dispositional awe on both online prosocial behavior and STML were greater for lower rather than higher SSES. This study extends the pro-sociality of dispositional awe to cyberspace. Other implications are also discussed herein.